French atheist spirituality - Skurzak, Joanna (Studia Philosophiae Christianae, 2020)
The phrase “atheist spirituality” may seem rather paradoxical at first. In practice, both atheists and theists object to it. Atheists would prefer to be called naturalists – in order to emphasize their connection with a specific tradition and interpretation of the world, and avoid being equated only with the denial of theism. They will be willing to deny the existence of any spiritual element, and thus deny the meaningfulness of religious language. It is worth stressing that this does not apply to all atheists. A new form of spirituality suggested by Francophone philosophers concerns first of all the resignation from a faith about a transcendent God, which is substituted with an undefined sacrum (what is holy, is highest) in immanence. New forms of spirituality are becoming a popular alternative to religious spirituality today. However, traditional and new spiritualities should not be treated as separate sets, as they do not necessarily compete with each other. Systems of spiritual development related to specific denominations will always provide inspiration even for atheist spirituality. The latter can indicate that apart from religion, there is also a spirituality that can develop in a person. Nihilism is not the only alternative to religion, as sometimes the defenders of the old religious order try to show. Atheist spirituality can sometimes refer to realities that are rich and enhancing. ------------- Otrzymano: 11/05/2020. Zrecenzowano: 20/06/2020. Zaakceptowano do publikacji: 30/06/2020